The Influence Of Marketing Strategy And Product Quality On Purchase Decisions Of Wardah Products At Toko Nyonya Kosmetik Pasar Lama Lahat - Elinda Anggriani; Nidyawati Nidyawati; Delvina Yulanda (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The purpose of this study was to determine the influence of marketing strategy and product quality on purchasing decisions for Wardah products at Nyonya Cosmetics Store, Pasar Lama Lahat. The variables in this study were marketing strategy (X1), product quality (X2), and purchasing decisions (Y). The data analysis methods used were instrument testing (reliability testing, validity testing), classical assumption testing (normality testing, heteroscedasticity testing, multicollinearity testing), multiple linear regression analysis, hypothesis testing (t-test and F-test), and coefficient of determination testing. the results of the study showed that (1) marketing strategy has a significant partial effect on purchasing decisions, as shown by the calculated t value > t table (7.120 > 1.989). (2) product quality has a significant partial effect on purchasing decisions, as shown by the calculated t value > t table (3.358 > 1.989). (3) Marketing Strategy and Product Quality have a significant simultaneous influence on Purchasing Decisions, as seen from the calculated f value > f table (60.936 > 3.987), and the significance value is smaller than the significance level (a) of 0.05 (0.000 < 0.05).